Проблеми формування товарної політики в умовах експортної блокади - Сударкіна, Світлана Петрівна; Кольвах, Вікторія Володимирівна (НТУ "ХПІ", 2015)
У статті розглядаються питання формування товарної політики промислових підприємств України. Досліджуються проблеми, стан та динаміка українського машинобудування. Розглядаються стратегії товарної політики залежно від типу ринку за рівнем конкуренції. Проводиться стислий огляд стану машинобудівної галузі та перспективи розвитку. Проводиться аналіз вирішення аналогічних проблем в інших країнах. Надаються шляхи та програми розвитку машинобудівної галузі України.

The article deals with the formation of commodity policy of the industrial enterprises of Ukraine. Investigate the causes of the problems and challenges of engineering as a one of the leading industries. The study, dynamics of the Ukrainian state, and mechanical engineering. It analyzes the importance of engineering for the Economy of the country. The influence of unstable Economy for the development of industry and mechanical engineering. Consider the strategy of commodity policy, depending on the type of market in terms of competition. A brief overview of the engineering industry. The prospects of development of heavy engineering. The analysis of solutions to similar problems in other countries. Are ways and programs of development of engineering industry of Ukraine.
Problems of commodity export policy under blockade
Keywords: промисловість; машинобудування; криза; конкуренція; програма державна; trade policy; industry; engineering; crisis; competition; state program